Against the Stream: Generalised anxiety disorder (GAD) – a redundant diagnosis. (1st March 2018) - Tyrer, Peter
Summary: The diagnosis of generalised anxiety disorder is a distraction of no value. It is highly unreliable, co-occurring with many other disorders of firmer diagnostic status, and has intrinsic connections to personality dysfunction. It is argued that classification would be heartily relieved to rid itself of this unnecessary appendage and for the symptom of anxiety to remain as a descriptive term only. Declaration of interest: None.